Student Information Security Awareness on the Use of ATM Machines - Komansilan, Trudi; Kumajas, Sondy C.; Pinatik, Triska (International Journal of Information Technology and Education, 2022)
This study examines literature studies on security systems at automated teller machines which include PIN security and forms of attacks on ATM security. The method used in ATM security is the use of a PIN to be able to access and make transactions through ATM machines. PIN security is carried out using a cryptographic process (encryption and decryption) using the Triple DES standard (data encryption standard). The use of ATMs is inseparable from the need to maintain a security system at ATMs. This document describes the use of DES and Triple DES cryptographic methods. Currently there are various threats that attack security in the use of ATMs such as skimming, phishing.